Factors that Inhibit the Development of Organisational Social Capital - Singh, Terence (My University, 2011)
The purpose of this research was to identify the major factors that inhibited the development of social capital between the different divisions of a corporate bank insofar as it related to the sharing of client-specific knowledge. This was investigated using a combination of both qualitative and quantitative data, the latter in the form of a survey instrument. The primary conclusions reached were that there were three main inhibiting factors, viz. Culture, Structure and Incentives. Culture was regarded as the most important factor with the remaining two factors being of lower but of approximately equal importance. The effect of demographics was found to have a weak influence on each of the above inhibiting factors. Only two significant differences were noted, viz. Incentives influenced PDIs (non-white) people more than Whites and that Structure was more important to females. It was also found that there were five clusters of respondents and that the racial profile was the point of significant difference in terms of demographic variables, between these clusters. To address these inhibiting factors, it was suggested that the relative importance of these be taken into account, i.e. that changing of Culture be addressed on a divisional and organisation-wide business. Further, the focus on incentive schemes is one that is short-term and needs to be considered very carefully since it may only serve to decrease, rather than increase, social capital in the long term. Finally, Structure is the easiest factor to address in that fairly simple interventions can be initiated to increase socialisation between divisions as well as physically cluster divisions that should work together more often by changing the layout of these within a building
MBA thesis - WBS
Keywords: Organizational social capital; Social capital